2011
DOI: 10.1074/jbc.m111.258053
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin Complex 2 (mTORC2) Negatively Regulates Toll-like Receptor 4-mediated Inflammatory Response via FoxO1

Abstract: Activation of the PI3K pathway plays a pivotal role in regulating the inflammatory response. The loss of mTORC2 has been shown to abrogate the activation of Akt, a critical downstream component of PI3K signaling. However, the biological importance of mTORC2 in innate immunity is currently unknown. Here we demonstrate that rictor, a key component of mTORC2, plays a critical role in controlling the innate inflammatory response via its ability to regulate FoxO1. Upon LPS stimulation, both rictor-deficient mouse e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
118
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 40 publications
15
118
0
Order By: Relevance
“…Rictor, an important component of mTORC2, contributes to glucose homeostasis in murine muscle tissue (Kumar et al, 2008), TORC2 C. elegans mutants show modulation of lifespan by affecting feeding and metabolism of different diets (Soukas et al, 2009), TORC2 is a mediator of proliferative and survival signals in cancer cells (Fang et al, 2012) and a study in mouse embryonic fibroblasts showed that mTORC2 regulates the TLR-mediated inflammatory response via FoxO1 (Brown et al, 2011). In addition, PRR5L, which is part of mTORC2, has been suggested to play a role in apoptosis in HeLa cells, but whether it is pro-apoptotic or antiapoptotic remains unclear (Thedieck et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Rictor, an important component of mTORC2, contributes to glucose homeostasis in murine muscle tissue (Kumar et al, 2008), TORC2 C. elegans mutants show modulation of lifespan by affecting feeding and metabolism of different diets (Soukas et al, 2009), TORC2 is a mediator of proliferative and survival signals in cancer cells (Fang et al, 2012) and a study in mouse embryonic fibroblasts showed that mTORC2 regulates the TLR-mediated inflammatory response via FoxO1 (Brown et al, 2011). In addition, PRR5L, which is part of mTORC2, has been suggested to play a role in apoptosis in HeLa cells, but whether it is pro-apoptotic or antiapoptotic remains unclear (Thedieck et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…While FoxO1 contributes to the expression of pro-inflammatory mediators (23,29), CREB is largely involved in the expression of anti-inflammatory mediators (25,41). Pharmacological activation of Akt corresponds with suppression of FoxO1 (42), which, in light of GSK3 suppression by Akt (26), points to a connection between GSK3 and FoxO1 activity.…”
Section: Differential Regulation Of Inflammatory Genes By Lps-mentioning
confidence: 99%
“…The anti-inflammatory effects of Akt on TLR4 signaling appear to be mediated through FoxO1 (23), suggesting that GSK3 may be important for the activation of FoxO1. GSK3 can potently suppress CREB (24).…”
mentioning
confidence: 99%
See 2 more Smart Citations